www.fltk.net > %1又2/3×(0.5%2/3)÷1又1/9

%1又2/3×(0.5%2/3)÷1又1/9

解: 原式=5/3×(2/3-1/2)÷10/9 =5/3×1/6×9/10 =(5×9)/(

图片

-一又2/3×(0.5-2/3)除以9/10 =-5/3×(-1/6)×10/9 =5/18×1

2又77/117

原式=[(8/27)^2/3-(49/9)^1/2+(1000/8)^2/3÷√50×4√2/10]

=-2/3+5又1/6+4又5/6-9又1/3 =(-2/3-9又1/3)+(5又1/6+4又5/6

原式=(3/2-2/3)*10/3*(1/5-1/2)*4/5 - 5/3*(1/2-2/3)*9/

=1.2x40x1.08+1.2x56.8=1.2(43.2+56.8)=1.2x100=120

见图

网站地图

All rights reserved Powered by www.fltk.net

copyright ©right 2010-2021。
www.fltk.net内容来自网络,如有侵犯请联系客服。zhit325@qq.com